2014
DOI: 10.1175/jas-d-13-0219.1
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity Evolution Leading to Tornadogenesis and Tornadogenesis Failure in Simulated Supercells

Abstract: A three-dimensional idealized cloud model was used to study the storm-scale differences between simulated supercells that produce tornado-like vortices and those that do not. Each simulation was initialized with a different Rapid Update Cycle, version 2 (RUC-2), sounding that was associated with tornadic and nontornadic supercells in nature. The focus is an analysis of vorticity along backward-integrated trajectories leading up to tornadogenesis (19 simulations) and tornadogenesis failure (14 simulations). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…It is generally accepted that the process of tornadogenesis involves vortices generated baroclinically by the rear flank downdraft that are then turned into the vertical (see, e.g., Naylor and Gilmore [2013], Markowski et al [2014]) and then potentially anchored at the surface. Recent numerical simulations of Orf et al [2014Orf et al [ , 2016 indicate two potentially important factors contributing to tornadogenesis: (a) consolidation of vertical vortices generated along the forward flank downdraft boundary and anchored at the surface that enter and strengthen the developing tornado; and (b) a streamwise current of horizontally generated vorticity that is tilted upward into the low-level mesocyclone.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the process of tornadogenesis involves vortices generated baroclinically by the rear flank downdraft that are then turned into the vertical (see, e.g., Naylor and Gilmore [2013], Markowski et al [2014]) and then potentially anchored at the surface. Recent numerical simulations of Orf et al [2014Orf et al [ , 2016 indicate two potentially important factors contributing to tornadogenesis: (a) consolidation of vertical vortices generated along the forward flank downdraft boundary and anchored at the surface that enter and strengthen the developing tornado; and (b) a streamwise current of horizontally generated vorticity that is tilted upward into the low-level mesocyclone.…”
Section: Introductionmentioning
confidence: 99%
“…Downdrafts (rather than updrafts) are considered important in generating near‐surface vertical vorticity by transporting vertical vorticity from mid‐levels to the surface (e.g. Rotunno and Klemp, ; Markowski and Richardson, ; Kosiba et al , ; Dahl et al , ; Markowski and Richardson, ; Naylor and Gilmore, ). Due to the deep‐layer wind shear and upper‐level winds, the bulk of the hydrometeors in a supercell is deposited on the forward flank of the main updraft.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The model took 27 min to form the supercell from the initial warm bubble. The formation of a supercell was defined as the earliest time when the 2-5-km integrated updraft helicity reached 900 m 2 s −2 , as introduced by Naylor and Gilmore [6]. After meeting the supercell criteria, the value of 2- The above analyses showed that the cloud model simulated the supercell and tornado reasonably well by using a real radiosonde background.…”
Section: Life Cycle Of the Simulated Tornadomentioning
confidence: 95%
“…However, the whole life cycle of a tornado from genesis to maintenance and demise, most notably in terms of the near-surface features, is hard to capture with observational data [3,4]. Relative to observations, numerical modeling can provide more thermodynamic information close to the tornado scale with higher spatial and temporal resolutions [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation